(2,7-Dimethoxynaphthalene-1,8-diyl)bis(4-fluorobenzoyl)dimethanone - Shoji Watanabe; Atsushi Nagasawa; Akiko Okamoto; Keiichi Noguchi; Noriyuki Yonezawa (Acta Crystallographica Section E, 2010)
The title compound, C26H18F2O4, is a naphthalene derivative in which the two aroyl groups at the 1- and 8-positions (peri positions) are anti to each other. There is an appreciable difference in the dihedral angles between the naphthalene ring system and the two benzene rings [66.88 (7)° and 88.09 (6)°]. In the crystal, weak C—H...O interactions involving one of the carbonyl groups and an aromatic C—H group ortho to the F atom seem to stabilize the packing of the molecules.